2010
DOI: 10.1007/s00280-010-1320-2
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II trial of the oral antiangiogenic agent TSU-68 in patients with advanced hepatocellular carcinoma

Abstract: TSU-68 at a dose of 200 mg bid determined by stratification into liver function, showed promising preliminary efficacy with a high safety profile in patients with HCC who had been heavily pre-treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 26 publications
2
57
1
Order By: Relevance
“…TSU-68, a tyrosine kinase inhibitor of PDGFR, FGFR and VEGFR, has revealed promising preliminary efficacy in a phase Ⅰ/Ⅱ trial of heavily pretreated advanced HCC patients, with a 13.1 mo OS and 2.1 mo TTP [40] . Another trial combining TSU-68 with TACE in patients with advanced HCC showed a trend towards prolonged PFS; however, this observation was not statistically significant [41] .…”
Section: Other Antiangiogenic Therapiesmentioning
confidence: 99%
“…TSU-68, a tyrosine kinase inhibitor of PDGFR, FGFR and VEGFR, has revealed promising preliminary efficacy in a phase Ⅰ/Ⅱ trial of heavily pretreated advanced HCC patients, with a 13.1 mo OS and 2.1 mo TTP [40] . Another trial combining TSU-68 with TACE in patients with advanced HCC showed a trend towards prolonged PFS; however, this observation was not statistically significant [41] .…”
Section: Other Antiangiogenic Therapiesmentioning
confidence: 99%
“…9,10 Our choice of TTP as study endpoint was based on the recommendation of an expert panel convened by the American Association for the Study of Liver Diseases. 11 The median time to tumor progression in this study was 12 weeks (range 4-32) (Figure 1(c)).…”
Section: Efficacymentioning
confidence: 99%
“…In a Phase I/II trial, Kanai et al reported an overall response rate of 51% with 2.9% complete response, 5.7% partial response and 42.8% stable disease. The median TTP was 2.1 months and median OS was 13.1 months [44]. Adverse events include diarrhea, malaise, and ALT / AST elevation, and were similar to other TKIs.…”
Section: Other Anti-angiogenic Agentsmentioning
confidence: 91%